Poverty's Effects on the Ability to Engage with Education Actively: A Case Study of the Access and Participation Plan - Afzal Sayed Munna (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The research investigates and understands how poverty creates risk and affects the ability to actively engage with education using a case study from an alternative provider's perspective—the research considered case study methods where data was collected using the qualitative research approach. The collection of data used data triangulation (focus groups and interviews of the students and senior staff members) using open-ended questions at the undergraduate level. The data were analyzed using Microsoft Excel to assess the impact poverty has on educational attainment. Different ethical aspects and challenges were considered during the research process to ensure anonymity, confidentiality, power, and authority. Based on the case study research, the institution developed their five years strategic plan, which submitting to the Quality Assurance Agency (QAA), Higher Education Funding Council for England (HEFCE), and also Office for Students (OFS) for their approval. The institution also introduced the Employers' Forum, which will continue to be effectively utilizing to enhance the student experience and retention and progression rates. The research only considered one case study institution and thus was limited to the data set. The research could have produced a comparative study if more institutions were choosing with a more significant data set.